The Magic school bus spins a web : a book about spiders - West, Tracey; Cole, Joanna; Degen, Bruce; Durk, Jim; Scholastic Productions, inc. (New York, NY : Scholastic, Inc., 1997)
Ms. Frizzle's class learns all about spiders while on a trip in the magic school bus.
"Based on an episode from the animated TV series produced by Scholastic Productions, Inc. ; based on The Magic school bus books written by Joanna Cole and illustrated by Bruce Degen"--T.p. verso.
At head of title: Scholastic's.
460
460
Accelerated Reader AR
Keywords: Spiders -- Juvenile literature